Plant Disease Detection: a Review of Current Trends - Gaganpreet Kaur, Mrs.; Kaur, Sarvjeet; Kaur, Amandeep (International Journal of Engineering and Technology, 2018)
Awareness of plant leaf diseases is very salient task in agricultural environment. The prior identification of plant leaf diseases can help to prevent the losses that farmers face due to various plant leaf diseases. The plant leaf diseases in image processing are detected by observing the patterns of leaf images at certain period of time. Observation and identification of leaf diseases is not an easy task to do manually because it requires a lot of time, money, effort etc. So it is better to identify the diseases through an automated system in image processing. There are various image processing techniques available for the detection of plant leaf diseases which consists of some basic steps such as, image acquisition, image pre-processing, image segmentation, feature extraction and image classification. Various types of filtering techniques can be used to de-noise the image so that the diseases can be detected efficiently and clearly because noise creates problems in identification of diseases. This paper presents a survey on various methods used for detection of plant leaf diseases in image processing. SomeÂ  segmentation techniques like thresholding, edge based, region based, clustering based and partial differential equation based are discussed.Â